Estimation of myocardial work from pressure–strain loops analysis: an experimental evaluation. (26th February 2018) - Hubert, Arnaud; Le Rolle, Virginie; Leclercq, Christophe; Galli, Elena; Samset, Eigil; Casset, Cyrille; Mabo, Philippe; Hernandez, Alfredo; Donal, Erwan
Abstract: Purpose: The area of left ventricular (LV) pressure–strain loop (PSL) is used as an index of regional myocardial work. The purpose of the present work is to compare the main segmental PSL markers and the derived global work indices, when they are calculated using an estimated pressure signal or an observed pressure signal. Methods and results: In nine patients implanted with a bi-ventricular pace-maker (CRT), LV pressure was invasively measured in five conditions: CRT-off, LV-pacing, right ventricular-pacing and two different CRT-pacing. For each condition, systolic blood pressure was measured by brachial artery cuff-pressure and transthoracic echocardiography loops were recorded simultaneously. The error and relative root mean square error (rRMSE) between measured and estimated pressure were calculated for each patient and each configuration. Correlation coefficient ( R 2 ) and Bland–Altman (BA) analysis were performed for PSL area and work indices. A total of 43 different haemodynamic conditions were compared (774 segmental PSL). The global rRMSE between estimated and measured LV-pressure was 12.3 mmHg. The estimated and measured segmental LV-PSL were strongly correlated, with an R 2 of 0.98. BA analysis shows that the mean bias for the estimation of segmental LV-PSL area is 86.0 mmHg.%. A significant bias effect with linearly increasing error with pressure values is observed. R 2  ≥ 0.88 and a mean bias in BA analysis ≤41.4 mmHg.% was observed for the estimation of global myocardial work indices. Conclusion: The non-invasive estimation for LV pressure–strain loop area and the global myocardial work indices obtained from LV-PSL strongly correlates with invasive measurements.